2014
DOI: 10.1517/14740338.2014.926888
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of medication administration errors with transdermal patches

Abstract: The systematic investigation of published errors illustrated that every step in the transdermal patch administration process is prone to errors. Thereby, the lack of knowledge and awareness of the importance of a correct administration practice were a major source of risk. Based on the identified errors and causes of errors prevention strategies were developed as a first step in avoiding transdermal patch administration errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Almost all dosage forms were described as predictive for administration errors or nonadherence in a specific context. The use of inhalers [19], injection devices [20][21][22], transdermal patches [23] and nasal preparations [24] and even of solid [25] or liquid [26] oral dosage forms was accompanied by administration errors. Furthermore, nonadherence was described for the use of ophthalmic preparations like eye drops [27], rectal preparations [28,29] such as suppositories and enemas as well as dermatological preparations (Table 1) [30,31].…”
Section: Dosage Formsmentioning
confidence: 99%
“…Almost all dosage forms were described as predictive for administration errors or nonadherence in a specific context. The use of inhalers [19], injection devices [20][21][22], transdermal patches [23] and nasal preparations [24] and even of solid [25] or liquid [26] oral dosage forms was accompanied by administration errors. Furthermore, nonadherence was described for the use of ophthalmic preparations like eye drops [27], rectal preparations [28,29] such as suppositories and enemas as well as dermatological preparations (Table 1) [30,31].…”
Section: Dosage Formsmentioning
confidence: 99%
“…One judge suggested adding the need to remove excess medication after removal of the patch. Experimental and systematic review studies have shown the risk of severe burns in cases where AED was used in patients with a nitrate drug patch, where the patch or excess medication was not withdrawn (28) .…”
Section: -Cardiac Rhythms Of Cardiopulmonary Arrest and Automatedmentioning
confidence: 99%
“…Good adhesion of a transdermal patch to the skin is essential for maximum efficacy, and adhesion failure hampers proper dosing 14. Consequently, and in the absence of any other rationale reason, skin adhesion problems may point practical reasons to explain an early replacement of fentanyl TTS and mimic end-of-dosage failure.…”
Section: Discussionmentioning
confidence: 99%